2005
DOI: 10.1016/j.femsle.2004.11.038
|View full text |Cite
|
Sign up to set email alerts
|

The riboflavin kinase encoding generibRofBacillus subtilisis a part of a 10 kb operon, which is negatively regulated by theyrzCgene product

Abstract: The riboflavin kinase encoding gene ribR is situated within a 12 genes locus ytmI-ytnM of the Bacillus subtilis chromosome. Here we demonstrate that ribR is transcribed as part of a 10 kb ytmI-ytnM operon. The riboflavin overproduction phenotype of B. subtilis ribC mutant strains, which is a result of the strongly reduced flavokinase activity of the riboflavin kinase/FAD synthetase RibC, was suppressed by ribR expression. Analysis of mutations with an upregulated ribR gene revealed 2 different groups of mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…A LysR homolog, encoded by a divergently oriented ytlI gene, exerts positive control over the ytmI operon (8), and Spx indirectly regulates ytmI expression by controlling the expression of the ytlI gene in medium containing sulfate. Recently, it was also reported that CymR is a negative regulator of the ytmI operon and ytlI gene expression (8,14,42). To investigate the role of CymR as a negative regulator for ytlI expression, we expressed the ytlIЈ-lacZ fusion (13) in wild-type (ORB5691), spx (ORB4871), and cymR mutant (ORB5733) strains.…”
Section: Resultsmentioning
confidence: 99%
“…A LysR homolog, encoded by a divergently oriented ytlI gene, exerts positive control over the ytmI operon (8), and Spx indirectly regulates ytmI expression by controlling the expression of the ytlI gene in medium containing sulfate. Recently, it was also reported that CymR is a negative regulator of the ytmI operon and ytlI gene expression (8,14,42). To investigate the role of CymR as a negative regulator for ytlI expression, we expressed the ytlIЈ-lacZ fusion (13) in wild-type (ORB5691), spx (ORB4871), and cymR mutant (ORB5733) strains.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of S. pombe and human RF kinases showed a novel family of phosphoryl-transferring enzymes (26,211). The role of monofunctional B. subtilis RF kinase in FMN synthesis in vivo has yet to be clarified (177,457,458). In addition to monofunctional RF kinases, bifunctional RF kinase/FAD synthetase is the main enzyme involved in eubacterial flavin nucleotide biosynthesis (101,280,286,320).…”
Section: Riboflavin Kinasementioning
confidence: 99%
“…According to Solovieva et al (2005), the expression of the ribR gene suppresses the riboflavin overproduction phenotype of Bacillus subtilis ribC mutant strains, which is a result of the strongly reduced flavokinase activity of the riboflavin kinase/FAD synthetase encoded by ribC. Sauer et al (1998) ) of inosine or guanosine (Debabov, 1982).…”
Section: Theoretical Backgroundmentioning
confidence: 99%